2007
DOI: 10.1007/s10482-007-9180-4
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal lactic acid bacteria in the mare: evaluation of the probiotic potential of native Lactobacillus spp. and Enterococcus spp. strains

Abstract: Lactic acid bacteria (LAB) are important members of the human vaginal microbiota and their presence is considered beneficial. However, little is known about native vaginal bacteria in other animal species such as the horse. The aim of this work was to quantify the vaginal lactic acid bacteria and lactobacilli of mares and to establish if selected equine vaginal lactic acid bacteria, particularly Lactobacillus and Enterococcus spp. strains, could exhibit potential as probiotics. The vaginal lactic acid bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 33 publications
3
27
0
4
Order By: Relevance
“…As the first step for LAB colonization is adhesion to the epithelial cell surface and formation of a biofilm (Ocana and Nader-Macias, 2002), there is a significant correlation between bacterial adhesion to the host cell surface and probiotic ability (Del Re et al, 1998, 2000Makras et al, 2006). In this study, we demonstrated these characteristics in LAB isolates from the intestinal tract of Muscovy duck, consistent with previous reports (Calderon et al, 2007;Mountzouris et al, 2007;Reddy et al, 2007;Fraga et al, 2008;Klose et al, 2010). Although only a few LAB isolates identified showed high levels of hydrophobicity and autoaggregation indices, we demonstrated that these properties are present in probiotics (Espeche et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…As the first step for LAB colonization is adhesion to the epithelial cell surface and formation of a biofilm (Ocana and Nader-Macias, 2002), there is a significant correlation between bacterial adhesion to the host cell surface and probiotic ability (Del Re et al, 1998, 2000Makras et al, 2006). In this study, we demonstrated these characteristics in LAB isolates from the intestinal tract of Muscovy duck, consistent with previous reports (Calderon et al, 2007;Mountzouris et al, 2007;Reddy et al, 2007;Fraga et al, 2008;Klose et al, 2010). Although only a few LAB isolates identified showed high levels of hydrophobicity and autoaggregation indices, we demonstrated that these properties are present in probiotics (Espeche et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…The ability to adhere to the epithelial cells and coaggregation ability are considered as important criterions for in vitro probiotic selection (15,33,34). Our results are in agreement with those of several authors (10,14).…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 , lactic acid and other organic acids produced by LAB are frequently associated with this activity in vitro (15). The inhibition of urogenital infections increases the relevance of these wild strains for use in probiotic products (39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations